Synthesis and crystal structure of a novel double 1：11 series arsenotungstate： [Cu^I（phen）2]5H6[Sm（AsW11O39）2]·6H2O - 王敬平 王伟 燕庆霞 牛景杨 (Journal of rare earths, 2008)
A novel double 1：11 series arsenotungstate, [Cu^I（phen）2]5H6[Sm（AsW11O39）2]·6H2O （phen=1, 10-phenanthroline） was synthesized by the hydrothermal method and characterized by elemental analysis, 1R spectra, and single-crystal X-ray diffraction. The title compound was monoclinic, space group P2 1/c, a=3.75710（2） nm, b=1.39776（8） nm, c=-3.33735（18） nm, β=96.967（10）°, V=17.3969（17） nm^3, Z=4. Single crystal X-ray structural analyses revealed that the dimeric polyanion, [SmAs2W22O78]^1-, consisted of one central Sm^3＋ ion and two tetradentate heteropoly ligands [ASW11O39]^7-. The Sm^3＋ ion and two tetradentate defective [AsW11O39]^7- anions were joined together by the sharing of four oxygen atoms from each heteropoly ligand. The bond valence sum （BVS） calculations of the title compound suggested that all four Cu atoms were in the ＋1 oxidation sate.